Cover Crop and Poultry Litter Management Influence Spatiotemporal Availability of Topsoil Nitrogen. Issue 6 (6th November 2015) - Poffenbarger, Hanna J.; Mirsky, Steven B.; Kramer, Matthew; Weil, Raymond R.; Meisinger, John J.; Cavigelli, Michel A.; Spargo, John T.
Abstract : Green and animal manures provide plant‐available N (PAN) in annual cropping systems and contribute to improved soil quality. Our objectives were to determine the effects of cover crop residue type and pelletized poultry litter (PPL) application method on: (i) the spatiotemporal distribution of topsoil mineral N (Nmin ), (ii) the average topsoil Nmin at four developmental stages of corn ( Zea mays L.), and (iii) corn N uptake. We collected soil and plant samples from a factorial experiment that included three cover crop residues: hairy vetch ( Vicia villosa Roth), cereal rye ( Secale cereale L.), and a hairy vetch/cereal rye mixture; and four PPL treatments: no PPL and 3.5 Mg PPL ha ‐1 either broadcast at planting, subsurface banded at the fifth‐leaf stage, or broadcast and incorporated at planting. Most of the Nmin in the broadcast treatment was concentrated near the soil surface, Nmin associated with the subsurface band remained within 10 cm of the delivery location throughout the growing season, while Nmin was distributed to a depth of 20 cm in the incorporated treatment. Average Nmin to 30 cm was significantly greater in soil with hairy vetch residue than in soil with cereal rye residue at emergence and the fifth‐leaf stage, while the cover crop mixture had average Nmin levels intermediate between the monocultures or similar to cereal rye depending on the year. In both years, corn N uptake tended to be greatest with hairy vetch residue and broadcast or subsurface band PPL application, averaging 215 kg ha ‐1 across years in these treatments.